The CXCL12/CXCR4 Signaling Axis Retains Neutrophils at Inflammatory Sites in Zebrafish - Isles, Hannah M.; Herman, Kimberly D.; Robertson, Anne L.; Loynes, Catherine A.; Prince, Lynne R.; Elks, Philip M.; Renshaw, Stephen A. (Frontiers in Immunology, 2019)
The inappropriate retention of neutrophils at inflammatory sites is a major driver of the excessive tissue damage characteristic of respiratory inflammatory diseases including COPD, ARDS and cystic fibrosis. The molecular programmes which orchestrate neutrophil recruitment to inflammatory sites through chemotactic guidance have been well studied. However, how neutrophil sensitivity to these cues is modulated during inflammation resolution is not understood. The identification of neutrophil reverse migration as a mechanism of inflammation resolution and the ability to modulate this therapeutically has identified a new target to treat inflammatory disease. Here we investigate the role of the CXCL12/CXCR4 signalling axis in modulating neutrophil retention at inflammatory sites. We used an in vivo tissue injury model to study neutrophilic inflammation using transgenic zebrafish larvae. Expression of cxcl12a and cxcr4b during the tissue damage response was assessed using in situ hybridisation and analysis of RNA sequencing data. CRISPR/Cas9 was used to knockdown cxcl12a and cxcr4b in zebrafish larvae. The CXCR4 antagonist AMD3100 was used to block the Cxcl12/Cxcr4 signalling axis pharmacologically. We identified that cxcr4b and cxcl12a are expressed at the wound site in zebrafish larvae during the inflammatory response. Following tail-fin transection, removal of neutrophils from inflammatory sites is significantly increased in cxcr4b and cxcl12a CRISPR knockdown larvae. Pharmacological inhibition of the Cxcl12/Cxcr4 signalling axis accelerated resolution of the neutrophil component of inflammation, an effect caused by an increase in neutrophil reverse migration. The findings of this study suggest that CXCR4/CXCL12 signalling may play an important role in neutrophil retention at inflammatory sites, identifying a potential new target for the therapeutic removal of neutrophils from the lung in chronic inflammatory disease.